2022
DOI: 10.3390/pharmaceutics14112370
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Vesicles Derived from Gut Microbiota and Probiotics: Cutting-Edge Therapeutic Approaches for Multidrug-Resistant Superbugs Linked to Neurological Anomalies

Abstract: Multidrug-resistant (MDR) superbugs can breach the blood–brain barrier (BBB), leading to a continuous barrage of pro-inflammatory modulators and induction of severe infection-related pathologies, including meningitis and brain abscess. Both broad-spectrum or species-specific antibiotics (β-lactamase inhibitors, polymyxins, vancomycin, meropenem, plazomicin, and sarecycline) and biocompatible poly (lactic-co-glycolic acid) (PLGA) nanoparticles have been used to treat these infections. However, new therapeutic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 198 publications
0
16
0
Order By: Relevance
“…Different from artificially assembled polypeptide vesicles, vesicles derived from the outer membrane of Gram-negative bacteria are called OMVs [ 17 , 18 , 19 , 20 ]. OMVs are widely produced, vary in size and composition, and contain soluble periplasmic content.…”
Section: Introductionmentioning
confidence: 99%
“…Different from artificially assembled polypeptide vesicles, vesicles derived from the outer membrane of Gram-negative bacteria are called OMVs [ 17 , 18 , 19 , 20 ]. OMVs are widely produced, vary in size and composition, and contain soluble periplasmic content.…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular vesicles (EVs), also known as membrane vesicles, are lipid-bilayer-enclosed particles with potential therapeutic use [ 80 ]. EVs produced by bacteria, notably LAB, are used in intercellular communication between the microbiota and the host.…”
Section: Resultsmentioning
confidence: 99%
“…Taking into account their biological properties, probiotic EVs could also be used for the treatment of certain neurological diseases. In fact, having the potential to cross the blood–brain barrier, they could represent efficient transporters for the delivery of drugs into the central nervous system [ 11 ]. Yuan et al [ 149 ] and Sun et al [ 150 ] extensively reported in their reviews the potential application of EVs-based strategies in the treatment of neurological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Although probiotics are currently in the center of interest of pharmaceutical concerns, more and more research focuses on searching for alternatives to these classically used products [ 8 , 9 ]. Difficulties in maintaining the viability of probiotics in commercial products and the fact that the viability of these microorganisms is not always necessary to obtain therapeutic effects have led to the concept of postbiotics [ 5 , 7 , 10 , 11 ]. Postbiotics are a mixture of metabolic products or non-viable fragments of probiotics that have a beneficial effect on the functioning of the human body [ 8 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation